Global surgery research collaborations during the COVID-19 pandemic - Anisa Nazir; Ramya Kancherla; Bright Huo; Brintha Sivajohan; Shaishav Datta; Amanpreet Brar; Ayesha Tasneem (Journal of Global Health Economics and Policy)
The COVID-19 pandemic created an unprecedented burden on health systems, including surgical services, which have been indirectly affected by the growing number of cases due to cancellation of operations, delayed screening and a lack of adequate resources such as PPE and ventilators. In addition to logistical challenges, the pandemic also raised imminent clinical questions that required immediate answers. Global collaborations have been vital to identifying challenges by pooling data and collecting evidence to provide critical information to guide clinical and surgical care. Research partnerships have been the driving force behind global surgery research; however, since the pandemic, there has been an increased need for equitable collaboration and innovation between high-income and low-income research institutions to continue making steady progress towards providing access to safe, affordable surgical care. This article explores academic research partnerships formed during the pandemic and identifies challenges and opportunities presented to researchers and institutions. Finally, this paper recommends that further collaborations be made between HIC and LMICs to ensure policies that global surgery ensures that key stakeholders are at the centre of research. Such policies need to focus on the access to education and mentorship, micro-grants for researchers, and publication opportunities.